The use of mycophenolate mofetil suspension in pediatric renal allograft recipients - Bunchman, Timothy; Navarro, Mercedes; Broyer, Michel; Sherbotie, Joseph; Chavers, Blanche; Tönshoff, Burkhard; Birk, Patricia; Lerner, Gary; Lirenman, David; Greenbaum, Laurence; Walker, Rowan; Zimmerhackl, Lothar B.; et al. (Pediatric nephrology, 2001)
Mycophenolate mofetil (MMF) is widely used to prevent acute rejection in adults after renal, cardiac, and liver transplantation. This study investigated the safety, tolerability, and pharmacokinetics of MMF suspension in pediatric renal allograft recipients. One hundred renal allograft recipients were enrolled into three age groups (33 patients, 3 months to <6 years; 34 patients, 6 to <12 years; 33 patients, 12 to 18 years). Patients received MMF 600 mg/m2 b.i.d. concomitantly with cyclosporine and corticosteroids with or without antilymphocyte antibody induction. One year after transplantation, patient and graft survival (including death) were 98% and 93%, respectively. Twenty-five patients (25%) experienced a biopsy-proven (Banff grade borderline or higher) or presumptive acute rejection within the first 6 months post-transplantation. Analysis of pharmacokinetic parameters for mycophenolic acid (MPA) and mycophenolic acid glucuronide showed no clinically significant differences among the age groups. The dosing regimen of MMF 600 mg/m2 b.i.d. achieved the targeted early post-transplantation MPA 12-h area under concentration-time curve (AUC0-12) of 27.2 µg h per ml. Adverse events had similar frequencies among the age groups (with the exception of diarrhea, leukopenia, sepsis, and anemia, which were more frequent in the <6 years age group) and led to withdrawal of MMF in about 10% of patients. Administration of MMF 600 mg/m2 b.i.d. is effective in prevention of acute rejection, provides predictable pharmacokinetics, and is associated with an acceptable safety profile in pediatric renal transplant recipients.